Job Stress, Ego Depletion, and Turnover Intention: The Buffering Role of Islamic Spiritual Well-Being in the Hospitality Industry - Jovinda Percillia Ma’rifatul Umairoh; Bagis, Fatmah; Hengky Widhiandono; Azmi Fitriati (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
High levels of work stress and employee turnover are classic problems in the hospitality industry that have serious implications for organizational sustainability. This study aims to analyze the effect of work stress on turnover intention through ego depletion, as well as test the role of Islamic Spiritual Well-Being (ISWB) as a moderation variable. This research is based on the Conservation of Resources (COR) Theory which emphasizes the importance of psychological resources in dealing with work pressure. The research population included 970 hotel and restaurant employees in the Purwokerto area, with a sample of 210 respondents selected using stratified random sampling techniques. The data was analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the study show that work stress has a positive effect on turnover intention both directly and indirectly through ego depletion. ISWB has been shown to moderate the relationship between work stress and turnover intention, where employees with high levels of Islamic spirituality show a lower tendency to leave work despite facing high stress. This research expands the application of COR Theory in the context of hospitality and makes a practical contribution to hotel and restaurant management in designing stress management programs based on Islamic spirituality.